REFERENSI ENDOFORA DALAM NOVEL HUJAN KARYA TERE LIYE - Noviadasari, Rani; Charlina, Charlina; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study titled is Endofora Reference in the novel of Hujan by Tere Liye. In general, the problem studied in this study is about the type of endofora reference based on the direction and type of object in the novel of Hujan by Tere Liye. This study aimed to describe the reference endofora in the novel of Hujan by Tere Liye. This research is very beneficial either pratically, theoretically and educationally. Operational definitions in this research are referent relations with symbols that represent them both based on the reference position and type of object. The research is a qualitative research with descriptive methods. This research data is the entire sentence that uses a reference endofora in the novel Hujan by Tere Liye. The data source of this study was obtained directly from the novel of Hujan by Tere Liye. Data obtained using the technique of record. Then, the data were analyzed by identifying and classifying based on a reference shape endofora novel text. From the data obtained in the novel of Hujan by Tere Liye, endofora reference forms are found among other personal references anaphora categories, demonstrative reference anaphora categories, comparative reference anaphora categories, personal references katafora categories, demonstrative reference katafora categories, and comparative references katafora categories. Types of personal pronouns used, among others, aku, saya, kamu, -mu, Anda, dia, ia, -nya, mereka, kita, and kalian. Kind of demonstrative pronouns used, among others, ini, itu, sini, and sana. While the comparative pronouns is used among other only sama.Key Words: Endofora references, novel, Hujan, Tere Liye